ANALYSIS OF THE DIMENSIONS OF PUBLIC SATISFACTION IN ONLINE BASED PUBLIC SERVICES AT THE ONE STOP INVESTMENT AND INTEGRATED SERVICES OFFICE - Merlitriaswati, Merlitriaswati; Mahsyar, Abdul; Daulay, Pardamean (Transpublika Publisher, 2025)
Technological development and advancement have influenced public services with the transition from conventional public services to online-based services, as implemented at the Investment and One-Stop Integrated Services Office (DPMPTSP) of Tana Toraja Regency. However, the online-based services that have been implemented still have many weaknesses. This research aims to analyze and describe the dimensions of public satisfaction in online-based public services. The research uses a qualitative approach with a case study type, and data is collected through interviews, observation, and documentation. Data is analyzed qualitatively using the Miles and Huberman model. The results show that the five dimensions of service quality according to Servqual theory meet public expectations. To improve online-based services according to public demands, several things need attention. First, the tangible dimension needs to be complemented with supporting facilities such as waiting rooms. Second, in the responsiveness dimension, service decreases when the number of residents being served is very high, necessitating additional staff, especially to serve residents who do not yet understand how to operate the application system. Third, the assurance dimension requires the provision of computer facilities that can be accessed directly by users and improved internet connectivity so that slow data transfer in online business licensing services through the OSS application can be enhanced. Fourth, the empathy dimension involves providing satisfactory services and helping citizens in need. This study suggests improving ICT capacity, increasing the number of employees, and enhancing employee knowledge and technical skills in using computer programs.